Plasmon-induced CD response of oligonucleotide-conjugated metal nanoparticles. - GOUNKO, IOURI; GERARD, VALERIE ANNE (My University, 2011)
Non-chiral metal nanoparticles conjugated with chiral oligonucleotide molecules demonstrated a circular dichroism (CD) at the plasmonic wavelengths due to aggregation effects.
PUBLISHED
Keywords: gold nanoparticle; nanocrystal; oligonucleotide; gold nanoparticle; nanocrystal; oligonucleotide